Data of winter weight from different subspecies of honey bee Apis mellifera colonies (Linnaeus, 1758) in southwestern Sweden - Norrström, Niclas; Niklasson, Mats; Leidenberger, Sonja (University of Skövde, 2021)
Honey bees are currently facing mounting pressures that have resulted in population declines in many parts of the world. In northern climates winter is a bottleneck for honey bees and a thorough understanding of the colonies’ ability to withstand the winter is needed in order to protect the bees from further decline. In this study the influence of weather variables on colony weight loss was studied over one winter (2019-2020) in two apiaries (32 colonies in total) in southwestern Sweden with weather stations recording wind, temperature, humidity and precipitation at 5-min intervals. Three subspecies of honey bees and one hybrid were studied: the native Apis mellifera mellifera, the Italian A. m. ligustica, the Carniolan A. m. carnica and the hybrid Buckfast. Additionally, we recorded Varroa mite infestation.
To analyze factors involved in resource consumption, three modelling approaches using weather and weight data were developed: the first links daily consumption rates with environmental variables, the second modelled the cumulative weight change over time, and the third estimated weight change over time taking light intensity and temperature into account.
Weight losses were in general low (0.039 ± 0.013kg/day and colony) and comparable to southern locations, likely due to an exceptionally warm winter (average temperature 3.5°C). Weight losses differed only marginally between subspecies with indications that A. m. mellifera was having a more conservative resource consumption, but more studies are needed to confirm this. We did not find any effect of Varroa mite numbers on weight loss.
In general, increasing light and temperature increase resource consumption in honey bees and within the temperature ranges of the experiment resource consumption was found to be in accordance with the master equation of metabolic theory of ecology (MTE). The effects of climate change could potentially affect the honey bees’ overwintering strategies and successes since temperature is expected to change but light intensity is expected to remain the same. A dependence on both light and temperature to guide resource consumption could thus potentially limit the honey bees’ ability to adapt to a changing climate.

Honungsbin står för närvarande inför flera utmaningar som har resulterat i att bipopulationer minskar i många delar av världen. I nordliga klimat är vintern en flaskhals för honungsbin och en fördjupad förståelse av koloniernas förmåga att stå emot vintern behövs för att skydda bipopulationerna från ytterligare nedgång. I denna studie studerades vädervariablers inflytande på bikoloniers viktminskning under vintern (2019-2020) i två bigårdar (totalt 32 kolonier) i sydvästra Sverige med väderstationer som registrerade vind, temperatur, luftfuktighet och nederbörd med 5 minuters intervall. Tre underarter av honungsbin och en hybrid studerades: den inhemska Apis mellifera mellifera, italienska bin A. m. ligustica, Carnicabin A. m. carnica och hybriden Buckfast. Dessutom registrerades kvalsterangrepp av Varroa.
För att analysera faktorerna som är inblandade i resurskonsumtion utvecklades tre modelleringsmetoder med hjälp av väder- och viktdata: den första länkade daglig förbrukningshastighet med miljövariabler, den andra modellerade den kumulativa viktförändringen över tid och den tredje uppskattade viktförändringen över tid kopplat till variablerna ljusintensitet och temperatur.
Viktminskningarna var i allmänhet låga (0,039 ± 0,013 kg/dag och koloni) och jämförbara med sydligare platser, troligen på grund av en exceptionellt varm vinter (medeltemperatur 3,5 ° C). Viktminskningarna skilde sig bara marginellt mellan underarter med indikationer på att A. m. mellifera hade en mer konservativ resursförbrukning, men fler studier behövs för att bekräfta detta. Vi fann ingen effekt av Varroa kvalster på viktminskning.
I allmänhet resulterade ökande ljus och temperatur i en ökande resursförbrukning hos honungsbina och inom temperaturområdena för experimentet överensstämmelse resultatet med huvudekvationen för metabolisk ekologisk teori (MTE). Effekterna av klimatförändringar kan eventuellt påverka honungsbinas övervintringsstrategier och framgång under övervintringar eftersom temperaturen förväntas förändras men ljusintensiteten förväntas förbli densamma. Ett beroende av både ljus och temperatur för att styra resursförbrukningen kan således potentiellt begränsa honungsbinas förmåga att anpassa sig till ett förändrat klimat.
Vintervikt hos olika underarter av honungsbikolonier Apis mellifera (Linné, 1758) i sydvästra Sverige
Winter weight data in honey bees
Keywords: Light intensity; Ljusintensitet; subspecies; underarter; Varroa mites; Varroa kvalster; Metabolism; Metabolism; temperature; temperatur; weight loss; viktminskning; Sweden; Sverige; overwintering; övervintring; Apis mellifera; Apis mellifera; honey bee; honungbi; non-linear mixed effect models; icke-linjära blandade effektmodeller; Natural Sciences; Naturvetenskap; Biological Sciences; Biologi; Zoology; Zoologi; Ecology; Ekologi